2019
DOI: 10.1016/j.foodchem.2019.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of water state during induced crystallization of honey

Abstract: This work studied water state of honey during crystallization, obtained statically and dynamically, by differential scanning calorimetry (DSC), water activity (a w ) assessment and time domain nuclear magnetic resonance (TD-NMR).Crystallization was induced by adding 5% of crystallized honey to three honey samples with different fructose/glucose ratio, the key characteristic for honey crystallization. Samples were stored at 14 °C.Dynamic crystallization was obtained by using an impeller. DSC showed that the dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…It was also observed that static crystallization is divided into two stages, with the second partially reversing the effects of the first. The study confirmed that in a dynamic process with continuous stirring, crystallization time of honey is reduced 5-6 times [48].…”
Section: Watersupporting
confidence: 75%
See 1 more Smart Citation
“…It was also observed that static crystallization is divided into two stages, with the second partially reversing the effects of the first. The study confirmed that in a dynamic process with continuous stirring, crystallization time of honey is reduced 5-6 times [48].…”
Section: Watersupporting
confidence: 75%
“…New methods of assessing moisture content in honey are based on evaluating the way of crystallization by studying crystal size and shape. Tappi et al [ 48 ] utilized Differential scanning calorimetry (DSC) and time domain magnetic resonance (TD-NMR) methods. The TD-NMR method allowed the authors to distinguish two pools of protons, whose relative intensity was approximately 55% and 45%.…”
Section: Methods For Assessing Bee Honey Qualitymentioning
confidence: 99%
“…Crystallization began when the seed was added, an agitation speed of 40 rpm, at room temperature (29-30 °C) for 24 h. The seeds were added 1% (280 g) by the weight of the glucose solution. The selection of crystallization conditions was based on Markande et al [12][13][14] and Flood and Srisanga [28]. The crystallization on each impeller was twice.…”
Section: Crystallization Processmentioning
confidence: 99%
“…Jha et al [9] and Besenhard et al [10] reported the modeling and controlling of the crystallization process. Sormoli et al [11] and Tappi et al [12] reported crystallization behavior during water induced. Parimaladevi and Srinivasan [13] reported the influence of supersaturation solution on the crystallization process.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As a supersaturated sugar solution, honey tends to spontaneously crystallize. The spontaneous crystallization of honey increases water activity, which can lead to unwanted fermentation (Tappi et al, 2019). The unwanted fermentation can negatively affect the quality of honey.…”
Section: Introductionmentioning
confidence: 99%